Identification of novel genetic susceptibility loci for Behcet's disease using a genome-wide association study - DİRESKENELİ, RAFİ HANER (BIOMED CENTRAL LTD, 2009)
Introduction Behcet's disease is a chronic systemic inflammatory disease that remains incompletely understood. Herein, we perform the first genome-wide association study in Behcet's disease. Methods Using DNA pooling technology and the Affymetrix 500K arrays, we identified possible candidate gene associations with Behcet's disease in a cohort of 152 Behcet's disease patients and 172 healthy ethnically matched controls. Genetic loci that were identified in the pooling study were genotyped in patients and controls using TaqMan genotyping technology. Results We identified genetic associations between Behcet's disease and single-nucleotide polymorphisms ( SNPs) in KIAA1529, CPVL, LOC100129342, UBASH3B, and UBAC2 ( odds ratio = 2.04, 2.26, 1.84, 1.71, and 1.61, respectively; P value = 4.2 x 10(-5), 1.0 x 10(-4), 3.0 x 10(-4), 1.5 x 10(-3), and 5.8 x 10(-3), respectively). Among the associated SNPs, the Behcet's disease-risk allele in rs2061634 leads to substitution of serine to cysteine at amino acid position 995 (S995C) in the KIAA1529 protein. Conclusions Using an unbiased whole-genome genetic association approach, we identified novel candidate genetic loci that are associated with increased susceptibility for Behcet's disease. These findings will help to better understand the pathogenesis of Behcet's disease and identify novel targets for therapeutic intervention.
Keywords: POLYMORPHISMS; HLA-B-ASTERISK-5101; STS-1